Micropropagation of white yam (Dioscorea rotundata Poir.) - Ng, S.Y.C. (Springer, 1992)
White yam (Dioscorea rotundata Poir.) belongs to the family Dioscoreaceae, genus Dioscorea. It is also known as white Guinea yam, Guinea yam, and 8-months' yam. The center of origin of white yam is in West Africa. D. rotundata, a cultigen, is so close to D. cayenensis that it has been regarded as a subspecies. It belongs to section Enantiophyllum, which comprises the most economically useful species of Dioscorea. D. rotundata appears to be of hybrid origin. It was speculated by Coursey (1976) that one parent is D. cayenensis, a forest species, adapted to a short dry season and having limited tuber dormancy. The other must be a savanna species, D. praehensilis, which bears the greatest resemblance to some D. rotundata forms, although D. abyssinica and D. togoensis may also have contributed. It was taken early in post-Columbian times to the West Indies, but it is not grown in Asia. The chromosome number is probably similar to D. cayenensis, as suggested by Purseglove (1976), and it was reported by Coursey (1976) as 2n = 2x = 40.